The labour market for histopathologists in KwaZulu- Natal: Emerging issues - Shaun Ruggunan (AOSIS, 2012)
The aim of this article was to assess the factors that shape the labour market for histopathologists in KwaZulu-Natal (KZN), South Africa. The literature on the labour market and labour processes of histopathologists is dominated by North American and European literature. This gap is most acutely felt on the African continent. This article attempts to fill this gap by shifting the focus towards understanding the factors that shape the professional milieu and labour market for histopathologists in South Africa. This study through a qualitative, descriptive and contextual design engaged in in-depth interviews with 70% of the population of histopathologists in KZN. The interviews were analysed thematically. These interviews were triangulated against labour market statistics for histopathologists in South Africa as well as a range of documentary evidence. The outcome of the study has demonstrated four key challenges facing the labour market for histopathologists: racial inequities persist in the labour market, gender inequities also persist, there is unfettered public-private sector mobility, and poor curriculum design at medical school level accounts for a limited input of registrars into the profession. The article concludes that there needs to be a shift from only studying the labour market and work organisation of clinical doctors to empirical research on the role of medical laboratory specialists in the healthcare chain, which will render South African histopathologists and their work visible. A set of labour market interventions is also suggested. Die artikel bestudeer die faktore wat die arbeidsmark vir histopatoloë in KwaZulu-Natal (KZN), Suid-Afrika beïnvloed. Die literatuur oor die arbeidsmark en arbeidsprosesse van histopatoloë word gedomineer deur Noord-Amerikaanse en Europese literatuur. Hierdie gaping is veral akuut op die Afrika kontinent. Die artikel poog om hierdie gaping te vul deur die fokus te verksuif na die faktore wat die professionele millieu en die arbeidsmark van histopatoloë in Suid-Afrika beïnvloed. Die studie het gebruik gemaak van 'n kwalitatiewe, beskrywende en kontekstuele ontwerp. In-diepte onderhoude is gevoer met 70% van die histopatoloë in KZN. Die onderhoude is tematies geanaliseer. Hierdie onderhoude is getrianguleer teen arbeidsmark statistieke vir histopatoloë in Suid-Afrika, sowel as 'n reeks dokumentêre bronne. Die uitkoms van die studie het vier belangrike struikelblokke geïdentifiseer wat die arbeidsmark vir histopatoloë in die gesig staar: rasse-ongelykhede duur voort in die arbeidsmark, so ook geslagsongelykheid, daar is vrylike beweging tussen die publieke- en privaatsektors, en 'n sleg ontwikkelde kurrikulum by mediese skole het lae toetrede getalle vir registrateurs in die professie tot gevolg. Die artikel kom tot die gevolgtrekking dat dit onvoldoende is om slegs die mark en werksoraganisasies van kliniese dokters te bestudeer - empiriese navorsing is ook nodig om die rol van die mediese labaratorium spesialiste in die gesondheidsorg ketting te bestudeer. 'n Stel arbeidsmark ingrypings word ook voorgestel.